Using springbok (Antidorcas) dietary proxies to reconstruct inferred palaeovegetational changes over 2 million years in Southern Africa. (February 2019) - Sewell, L.; Merceron, G.; Hopley, P.J.; Zipfel, B.; Reynolds, S.C.
Abstract: The reconstruction of past vegetation and climatic conditions of the Cradle of Humankind, Gauteng Province, South Africa, has been approached using various proxies (such as micromammals, speleothems, faunal and floral presence and stable carbon isotopes). Elisabeth Vrba's seminal studies (1974; 1975) on the fossil record of this region indicated dramatic faunal turnover based on species extinction and speciation data. This turnover was thought to have been driven by increasing aridity and spreading grasslands. These reconstructions however, are continuously being refined and adapted in light of advancing techniques (such as dental microwear textural analysis) and terrestrial proxies, such as speleothems. However, more recent studies show varying proportions from wooded towards more grassland-dominated habitats, with the most common reconstruction being the heterogeneous 'mosaic' habitat. Here we re-evaluate the findings of a transition from woodland to grassland conditions in the fossil record from Member 4 Sterkfontein to Member 5 Sterkfontein and the deposits of Swartkrans. To approach the palaeovegetation changes through time via a different angle, we focus on the diet of the springbok (genus Antidorcas ), represented throughout this temporal period from geological members dating from 2.8–0.8 Ma. We use detailed dietary methods (dental linear measurements, mesowear, microwear, and stable carbon isotope analysis) to explore past changes in diets of springbok that can be used to indicate the prevailing vegetation conditions. Our results presented here broadly agree with previous palaeoenvironmental reconstructions, in indicating increased grassland post ca 1.7 Ma, with some suggestion of more heterogeneous habitats for Swartkrans Member 2 (ca 1.65–1.07 Ma). We find that there is support for the implementation of a multi-disciplinary approach to produce more accurate and robust reconstructions of past diets and by extension, of palaeovegetation conditions, if the selected herbivore species is a mixed-feeder, like the springbok. Highlights: A multi-method approach to palaeoenvironmental questions is beneficial. All DMTA data supports Antidorcas being a predominantly mixed feeding genus. More heterogeneous habitats are indicated for Swartkrans Member 2. A single lineage approach can provide comparable results to other approaches.